Applied econometric time series - Enders, Walter (Hoboken, NJ : Wiley, 2010)
This new edition reflects both sound structure and recent advances in time series econometrics, such as out-of-sample forecasting techniques, nonlinear time-series models, Monte Carlo analysis, and bootstrapping.
Includes bibliographical references (p. 495-502) and index.
oif 26/11/13
Loan
Keywords: Econometrics; Time-series analysis